DOI: 10.22215/etd/2014-10346
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Blast Loading on Seismically Detailed Reinforced Concrete Columns

Abstract: The rise in the number of terrorist attacks over the past few decades has led to growing concerns about the performance of buildings designed by well-established conventional design methods under blast loading. The concerns arise from the response of buildings and loss of lives in some of the more popular terrorist attacks such as those involving the Alfred P. Murrah Building, the Khobar Towers, and Marriott Hotel in Islamabad. Whereas most damage during these attacks was to non-structural elements such as inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 43 publications
(74 reference statements)
1
12
0
Order By: Relevance
“…As expected, the lateral displacements increased with increasing the charge mass at constant scaled distance. Similar observations were reported by Kyei [11]. Comparison of failure modes for conventional and seismically column, shown in Figure 13, indicates that the failure shape of seismically detailed column is better than that of the conventional column, showing only crushing and spalling of the concrete cover while the internal concrete core was confined enough without any crushing.…”
Section: Numerical Results and Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…As expected, the lateral displacements increased with increasing the charge mass at constant scaled distance. Similar observations were reported by Kyei [11]. Comparison of failure modes for conventional and seismically column, shown in Figure 13, indicates that the failure shape of seismically detailed column is better than that of the conventional column, showing only crushing and spalling of the concrete cover while the internal concrete core was confined enough without any crushing.…”
Section: Numerical Results and Discussionsupporting
confidence: 84%
“…It is therefore essential to direct research to improve the resistance of columns to blast so as to provide protection to the structure [7,8]. Several researchers investigating experimentally the behavior of RC columns under near-field explosion showed that seismic detailing of RC columns has noticeable effect on the blast behavior [9][10][11]. Abladey and Braimah [10] investigated the effects of near-field explosions on RC columns and showed that RC columns designed and detailed for areas of high seismicity detailed reinforcement have a high blast resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The examples presented here illustrate important differences between the various models in addition to illustrating some key concrete behaviours that the models should be able to capture. Kyei [90] was validated numerical simulation with experimental work conducted by Farouk [91].…”
Section: Numerical Examples and Comparison With Experimental Resultsmentioning
confidence: 99%
“…Kyei [26] investigated the responses of RC columns originally designed and detailed with sufficient ductility for a given magnitude of earthquake in a specific zone. The columns were modelled using various seismic detailing rules as well as conventional details and a comparison of the responses was investigated.…”
Section: Performance Of a Seismically Designed Sdof Model Under Blastmentioning
confidence: 99%